2011
DOI: 10.1039/c1sm05096f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale condensation of water on self-assembled monolayers

Abstract: We demonstrate that water is almost universally present on apparently dry self-assembled monolayers, even on those considered almost hydrophobic by conventional methods such as water contact goniometry. The structure and kinetics of nanoscale water adsorption onto these surfaces were investigated using X-ray and neutron reflectometry, as well as atomic force microscopy. Condensation of water on hydrophilic surfaces under ambient conditions formed a dense sub-nanometre surface layer; the thickness of which incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
127
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(148 citation statements)
references
References 62 publications
20
127
0
1
Order By: Relevance
“…In typical conditions the humidity is so large that several water layers form on any surface. 39,40 The effect of this is a drastic lowering of Q and the dramatic increase of E ts where the tip is close enough to the surface to resolve atoms. This can be seen by the large excitation required in Fig.…”
Section: B Effect Of Hydration Layer On Dampingmentioning
confidence: 99%
See 1 more Smart Citation
“…In typical conditions the humidity is so large that several water layers form on any surface. 39,40 The effect of this is a drastic lowering of Q and the dramatic increase of E ts where the tip is close enough to the surface to resolve atoms. This can be seen by the large excitation required in Fig.…”
Section: B Effect Of Hydration Layer On Dampingmentioning
confidence: 99%
“…Laboratory air also has a significant amount of water vapor, where the partial pressure of water depends on temperature and relative humidity (RH). If RH is greater than zero, all surfaces (hydrophobic or hydrophilic) exposed to air 39,40 adsorb a water layer with a thickness dependent on the exposure time, temperature, RH, and the sample's hydrophilic or hydrophobic character. showed that by poking the surface, the tip could be used to create monoatomic terraces due to plastic deformation of the KBr(001) cleavage plane in UHV.…”
Section: Ambient Conditions: the Hydration Layermentioning
confidence: 99%
“…Similarly, the thickness of brine films on silica increased over 100 times with surface roughness [104]. Multilayer adsorption is observed on rather hydrophobic self-assembled monolayers, from d ~ 2 nm at low humidity up to 4 nm at 65% RH [105,106]. Steps in mica terraces lead to nucleation of water deposits of height of 7 nm at 65% RH [107].…”
Section: Wetting Film Thicknessmentioning
confidence: 90%
“…In addition, the volume of water molecules confined to 5.1 and 2.8 nm TiO 2 pores increases by 4 and 7.5 %, respectively, with respect to that in the bulk [55]. More interestingly, a monolayer film of water at room temperature manifests 'quasi-solid' and hydrophobic nature that prevents the monolayer water from being wetted by a water droplet [21,56].…”
Section: Observationsmentioning
confidence: 99%